Leveraging Vlog to Enhance Secondary School Students’ Speaking Performance - Ahmad Jumeidi; Rahma Dianti (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
These days technology is available to assist many facets of education. A vlog is a well-known technology tool used by many people globally to express themselves. This study aimed to explore whether Vlogging implementation as a learning media can significantly leverage secondary students’ speaking performance. This study also aimed to examine whether Vlogging implementation is more effective rather than another approach in improving students’ speaking performance. Quasi-experimental research was employed as the design in carrying out this study. The research participants were 77 students chosen using the purposive sampling technique. A spoken test was administered to gather the data. The obtained data were analyzed using a Paired sample t-test and independent sample t-test. The paired sample t-test results showed that Vlog implementation could significantly leverage the student’s speaking performance. The results of the independent sample test also revealed a significant difference in the students’ speaking performance between the students who were using vlog as a learning media and those who were using a conventional method.